The Basic For an Islamic Oriented Tertiary Education Curriculum in Psychology - Wismaningsih Sudrajat; Kusdwiratri Setiono (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 1996)
The goal of higher education in Psychology is to produce psychologists capable of conducting research and assisting people to solve their psy chological problems. Psychology as a scientific discipline originated from Western countries. The use of Western psychological concepts and theories has met with much criticism, because not ail fit in the Islamic world.Based on the above, it is proposed that the curriculum tor tertiary education in Psychology should consist of 60% Western Psychology (Contemporary Psychology) and 40 % Islamic adaptation. This stra tegy will give the opportunity for psychologists graduating from this pro gram to keep up with the state of the art Contemporary Psychology, as well as getting the opportunity to do research to adapt psychological concepts and theories to the Islamic world view. The rationale and elaboration of the proposed Indonesian Islamic Psychology Curriculum willbe discussed as a model.